Thiacalix [4] arene protected copper-silver nanocluster material for electroreduction of CO2 and preparation method of thiacalix [4] arene protected copper-silver nanocluster material

Through the design and synthesis of copper-silver nanocluster materials for thio cup [4] aromatic hydrocarbon protection, the problem of difficulty in taking into account the activity and stability of silver nanoclusters during catalytic CO2 reduction is solved, and efficient, stable and economical catalytic effects are achieved.

CN119775586AActive Publication Date: 2025-04-08NORTHEAST NORMAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510055224.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-08
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

In the prior art, silver nanoclusters are difficult to take into account both the activity and stability of the catalytic reduction, resulting in insufficient catalytic efficiency and economicality.

Method used

The copper-silver nanocluster material was protected by sulfur cup[4] aromatic hydrocarbons, and the copper-silver nanocluster material was directly synthesized through one pot of solvent heat. A high symmetry topological structure was designed, and the Oh dual drive was used to form a molecular structure composed of the inorganic silver core and peripheral ligand.

Benefits of technology

Efficient CO2 reduction catalysis is achieved, high yield, CO Faraday efficiency reaches 97.76%, and the stability of the catalyst is maintained, simplified the synthesis process and improved economicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775586A_ABST
    Figure CN119775586A_ABST
Patent Text Reader

Abstract

The invention discloses a thiacalix [4] arene protected copper-silver nanocluster material for electroreduction of CO2 and a preparation method of the thiacalix [4] arene protected copper-silver nanocluster material, and belongs to the technical field of organic-inorganic hybrid catalysts. The copper-silver nanocluster material is directly synthesized by adopting a simple one-pot solvothermal method, the operation is simple and convenient, the period is short, and the yield is high. The prepared copper-silver nanocluster material has Oh symmetry, the molecular structure of the copper-silver nanocluster material is composed of a truncated cube inorganic silver inner core and peripheral ligands, large ligands cover and passivate large faces in the cube inner core, small ligands cover and passivate small faces in the cube inner core, and a double-hydrophobic protection shell is formed. And silver atoms of the chamfered surfaces are exposed, so that symmetrical construction of the cluster structure and ordered exposure of sites are realized, and synthesis of the copper-silver nanocluster material with both stability and activity is effectively ensured. The Faraday efficiency of reducing CO2 into CO through electro-catalysis under the condition that the copper-silver nanocluster material is stable reaches 97.76%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic-inorganic hybrid catalysts, and in particular relates to a thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2 and a preparation method thereof. Background Art

[0002] Silver-based metal catalysts occupy an important position in the field of catalysis. Compared with bulk silver materials and silver nanoparticles, silver nanocluster materials have smaller sizes, atomically precise structures and modifiable surface ligands, and are widely used in the field of electrocatalytic CO2 reduction. Silver nanoclusters are composed of peripheral ligands and internal silver cores. The ligands can protect and stabilize the silver core, but on the other hand, they may cause the metal core to be over-covered and thus passivate the active center. Therefore, the activity and stability of silver nanoclusters often cannot be taken into account at the same time. How to design and synthesize silver nanoclusters with both high stability and high activity is still quite difficult.

[0003] Patent 1: 202111041710.5; Document 2: Sci. Adv. 2016, (Issue 2), e1600323; Document 3: [1] Guan Zongjie. Synthesis, structure and properties of coin metal nanoclusters protected by calixarene and alkyne ligands [D].; Document 4: Chemical Science, 2024, 15, 7643-7650. The method of using thiacalix[4]arene to protect silver clusters is mentioned. Patent 1 and Document 2 mention its application in fluorescence, but there are no specific examples of its application in the field of catalysis. The reason is that stability and activity cannot be taken into account at the same time. Document 3 systematically introduces the synthesis method of thiacalix[4]arene protected silver clusters and preliminary application exploration. However, the synthesis method is relatively cumbersome, usually involving multi-step synthesis, and the yield is low. The poor economic efficiency leads to its rare application in the field of catalysis. Reference 4 mentions the electrocatalytic reduction of CO2 by a Zr / Ag bimetallic cluster protected by calixarene. However, the bimetallic cluster has only a few exposed active silver atoms, the molecular structure is not sufficiently ordered, and the Faraday efficiency of carbon monoxide does not reach more than 95%.

[0004] Therefore, a new technical solution is urgently needed in the prior art to solve this problem. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2 and a preparation method thereof to solve the technical problem that the activity and stability of the silver nanoclusters in the prior art cannot be taken into account at the same time.

[0006] A thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2, wherein the single molecule chemical formula of the copper-silver nanocluster material is:312 H 372 Ag 54 Cu 24 O 153 S 56 ; The single molecule structure formula of copper-silver nanocluster material is: Cu 24 Ag 54 (TC4A)6(SO4) 32 ( t BuC≡C) 12 , where TC4A represents thiacalix[4]arene, t BuC≡C is tert-butylacetylene; The first is a cubic crystal system with a space group of Pn-3 and a unit cell parameter of: a = 40.4478 , b = 40.4478 , c = 40.4478 , α = 90°, β = 90°, γ = 90°, V = 66173.6 ; The second is a trigonal system, space group R-3, unit cell parameter a = 28.878 , b = 28.878 , c =66.254 , α = 90°, β = 90°, γ = 120°, V = 47849 ; The third is tetragonal system, space group P4 / mnc, unit cell parameter: a = 27.5065 , b = 27.5065 , c = 46.6184 , α = 90°, β = 90°, γ = 90°, V = 35271.8 ; Among them, a, b, c represent the axial lengths of the three groups of unit cells, α, β, γ represent the axial angles of the crystal, and V represents the volume of each unit cell.

[0007] A method for preparing a thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2, comprising the following steps, and the following steps are performed in sequence: Step 1, dissolving organic silver acetylene, copper sulfate pentahydrate and thiacalix[4]arene in a mixed solvent, and stirring to obtain a mixture; Step 2: Transfer the mixture in step 1 to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it; Step 3: After tightening the stainless steel autoclave in step 2, transfer it to an electric hot air drying oven and keep it at 80 to 100 degrees Celsius for 1 to 3 days, then cool it naturally to room temperature, and take out the orange-yellow block crystals appearing in the polytetrafluoroethylene lining; Step 4: Wash the block crystals obtained in step 3 with acetonitrile and dry them at room temperature to obtain the copper-silver nanocluster material.

[0008] The organic silver acetylide in step 1 is at least one of alkyl silver acetylide or phenyl silver acetylide.

[0009] The thiacalix[4]arene in step 1 is at least one of 4-tert-butyl-thiacalix[4]arene, 4-phenyl-thiacalix[4]arene or thiacalix[4]arene.

[0010] The mass ratio of copper sulfate pentahydrate, organic silver acetylene and thiacalixarene in the step 1 is 3:2:2 to 3:1:1.

[0011] The mixed solvent in step 1 is a nitrogen-containing solvent, an alcohol and a third solvent, and the mass ratio of the three is 1:1:2 to 1:4:4.

[0012] The nitrogen-containing solvent is N,N-dimethylformamide or N,N-diethylformamide or N,N-dimethylacetamide; the alcohol is methanol or ethanol or n-butanol or isopropanol or n-propanol; the third solvent is acetonitrile or tetrahydrofuran or 1,4-dioxane.

[0013] The total mass of the copper sulfate pentahydrate, the organic silver acetylene and the thiacalix[4]arene is 50 mg to 100 mg, and the total volume of the mixed solvent used is 2 ml to 6 ml.

[0014] Through the above design scheme, the present invention can bring the following beneficial effects: 1. The present invention adopts a simple one-pot solvent-thermal method to directly synthesize copper-silver nanocluster materials, which is easy to operate, short in cycle, and high in yield. The yield can be greater than 75% based on silver acetylene. Compared with the synthesis methods of Patent 1, Document 2 and Document 3 in the background technology, it is simpler and more convenient, and can greatly improve the synthesis efficiency of metal nanocluster materials.

[0015] 2. The catalyst material obtained in the present invention is a crystalline material, which can be tested by an X-ray single crystal diffractometer to obtain its definite molecular formula and molecular structure.

[0016] 3. The present invention utilizes a highly symmetrical topological structure to design the catalyst, which is unprecedented in the above literature and patents and in the art. O h The copper-silver nanocluster material described in the present invention is obtained by dual driving. The copper-silver nanocluster material isO h Symmetry, its molecular structure consists of a truncated cubic inorganic silver core and peripheral ligands. During the synthesis process, the thiacalix[4]arene chelates the tetranuclear copper and four sulfate groups to form a large ligand, which covers or passivates the larger face of the cubic core. The alkyne ligand is smaller in size and covers or passivates the smaller face of the cubic core, forming a double hydrophobic protective shell. The silver atoms on the truncated face are exposed, achieving the symmetrical structure of the cluster structure and the orderly exposure of the sites, effectively ensuring the synthesis of copper-silver nanocluster materials that take into account both stability and activity.

[0017] 4. The catalyst obtained by the present invention is used for catalytic CO2 reduction, and has a smaller charge transfer resistance, higher selectivity, and lower overpotential, so that it can maintain a CO Faraday efficiency of more than 80% at a potential of -0.95 to -1.25 V vs RHE under the condition of potassium chloride as the electrolyte, especially at a voltage of -1.15 V vs RHE, it can reach a CO Faraday efficiency of 97.76%, which is higher than the 90.23% of the document 4 in the previous background technology.

[0018] 5. The catalyst obtained by the present invention is used for catalytic CO2 reduction, and can achieve 100 mA cm in the flow cell. -2 ~300 mAcm -2 The CO Faradaic efficiency can reach over 70% at high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention is further described below with reference to the accompanying drawings and specific embodiments: Figure 1 A ball-and-stick model diagram of the single-molecule structure of the copper-silver nanocluster material determined by a single crystal diffraction experiment in a thiacalix[4]arene-protected copper-silver nanocluster material for electroreduction of CO2 and a preparation method thereof according to the present invention; Figure 2 A single-molecule atomic space filling diagram of the copper-silver nanocluster material protected by thiacalix[4]arene for electroreduction of CO2 and a preparation method thereof determined by a single crystal diffraction experiment; Figure 3 A comparison diagram of the current density of the copper-silver nanocluster material protected by thiacalix[4]arene for electroreduction of CO2 in the present invention and the preparation method thereof in a linear sweep voltammetry test under a CO2 / Ar atmosphere; Figure 4 A thiacalix[4]arene protected copper-silver nanocluster material for electro-reduction of CO2 and a preparation method thereof of the present invention shows the products of electro-catalytic CO2 reduction of the copper-silver nanocluster material at different potentials and its Faraday efficiency diagram; Figure 5The product of electrocatalytic CO2 reduction of the copper-silver nanocluster material at different current densities in a flowing electrolytic cell in a thiacalix[4]arene-protected copper-silver nanocluster material for electroreduction of CO2 and a preparation method thereof of the present invention, as well as the CO Faraday efficiency and CO partial current density diagram; Figure 6 The X-ray powder diffraction pattern (PXRD) of the copper-silver nanocluster material protected by thiacalix[4]arene for electroreduction of CO2 of the present invention and the preparation method thereof; Figure 7 The infrared spectrum of the copper-silver nanocluster material protected by thiacalix[4]arene for electroreduction of CO2 and the preparation method thereof is shown in FIG. DETAILED DESCRIPTION Example

[0020] Dissolve 10 mg of tert-butyl acetylide silver, 30 mg of copper sulfate pentahydrate and 10 mg of tert-butyl thia-calix [4] arene in a mixed solvent of 0.5 ml of N, N-dimethylformamide, 0.5 ml of ethanol and 1 ml of acetonitrile, and stir evenly. Then transfer the mixture to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it. Tighten the autoclave and transfer it to an electric heated blast drying oven. After keeping it at 80 degrees Celsius for 1 day, it is naturally cooled to room temperature, and a large number of orange-yellow block crystals appear. After washing the obtained crystals with acetonitrile and drying at room temperature, the copper-silver nanocluster material is obtained, which belongs to the tetragonal system and has a yield of 81% based on acetylide silver. Example

[0021] Dissolve 10 mg of tert-butyl acetylide silver, 15 mg of copper sulfate pentahydrate and 10 mg of phenylthiacalix[4]arene in a mixed solvent of 0.5 ml of N,N-dimethylformamide, 0.5 ml of ethanol and 1 ml of acetonitrile, and stir evenly. Then transfer the mixture to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it. Tighten the autoclave and transfer it to an electric heated blast drying oven. After keeping it at 90 degrees Celsius for 1 day, it is naturally cooled to room temperature, and a large number of orange-yellow block crystals appear. After washing the obtained crystals with acetonitrile and drying at room temperature, the copper-silver nanocluster material is obtained, which belongs to the trigonal system and has a yield of 76% based on acetylide silver. Example

[0022] 20 mg of tert-butyl acetylide silver, 30 mg of copper sulfate pentahydrate and 10 mg of tert-butyl thia-calix [4] arene were dissolved in 0.5 ml of N, N-dimethylacetamide, 0.5 ml of ethanol and 1 ml of acetonitrile mixed solvent and stirred evenly. Then the mixture was transferred to the polytetrafluoroethylene liner of a stainless steel autoclave and the lid was buckled. The autoclave was tightened and transferred to an electric heated blast drying oven. After being kept at 100 degrees Celsius for 1 day, it was naturally cooled to room temperature, and a large number of orange-yellow block crystals appeared. The obtained crystals were washed with acetonitrile and dried at room temperature to obtain the copper-silver nanocluster material, which belongs to the cubic system and has a yield of 83% based on acetylide silver. Example

[0023] Dissolve 20 mg of tert-butyl acetylide silver, 50 mg of copper sulfate pentahydrate and 20 mg of tert-butyl thia-calix [4]arene in 1 ml of N,N-dimethylformamide, 1 ml of ethanol and 2 ml of acetonitrile mixed solvent and stir evenly. Then transfer the above mixture to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it. Tighten the autoclave and transfer it to an electric heated blast drying oven. After keeping it at 100 degrees Celsius for 1 day, it is naturally cooled to room temperature, and a large number of orange-yellow block crystals appear. The obtained crystals are washed with acetonitrile and dried at room temperature to obtain the copper-silver nanocluster material, which belongs to the cubic system and has a yield of 87% based on acetylide silver. Example

[0024] Dissolve 20 mg of cyclohexyl acetylide silver, 60 mg of copper sulfate pentahydrate and 20 mg of tert-butylthiacalix[4]arene in a mixed solvent of 0.5 ml of N,N-dimethylformamide, 2 ml of methanol and 2 ml of acetonitrile, and stir evenly. Then transfer the above mixture to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it. Tighten the autoclave and transfer it to an electric heated blast drying oven. After keeping it at 100 degrees Celsius for 1 day, it is naturally cooled to room temperature, and a large number of orange-yellow block crystals appear. After washing the obtained crystals with acetonitrile and drying at room temperature, the copper-silver nanocluster material is obtained, which belongs to the cubic system and has a yield of 79% based on acetylide silver. Example

[0025] 20 mg of phenylacetylene silver, 55 mg of copper sulfate pentahydrate and 20 mg of 4-phenylthia cupric [4] arene were dissolved in 1 ml of N, N-dimethylformamide, 2.5 ml of n-butanol and 2.5 ml of tetrahydrofuran mixed solvent and stirred evenly. Then the mixture was transferred to the polytetrafluoroethylene liner of a stainless steel autoclave and the lid was buckled. The autoclave was tightened and transferred to an electric blast drying oven. After being kept at 90 degrees Celsius for 1 day, it was naturally cooled to room temperature, and a large number of orange-yellow block crystals appeared. The obtained crystals were washed with acetonitrile and dried at room temperature to obtain the copper-silver nanocluster material, which belongs to the trigonal system and has a yield of 84% based on acetylene silver. Example

[0026] Dissolve 10 mg of tert-butyl acetylide silver, 30 mg of copper sulfate pentahydrate and 10 mg of tert-butyl thia-calix [4] arene in a mixed solvent of 0.5 ml of N,N-dimethylformamide, 1 ml of isopropanol and 1 ml of acetonitrile, and stir evenly. Then transfer the above mixture to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it. Tighten the autoclave and transfer it to an electric heated blast drying oven. After keeping it at 80 degrees Celsius for 1 day, it is naturally cooled to room temperature, and a large number of orange-yellow square crystals appear. The obtained flaky crystals are washed with acetonitrile and dried at room temperature to obtain the copper-silver nanocluster material, which belongs to the tetragonal system and has a yield of 83% based on acetylide silver. Example

[0027] Dissolve 10 mg of phenylacetylene silver, 30 mg of copper sulfate pentahydrate and 10 mg of thia-calix[4]arene in 1 ml of N,N-dimethylacetamide, 1 ml of ethanol and 4 ml of dioxane mixed solvent and stir evenly. Then transfer the above mixture to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it. Tighten the autoclave and transfer it to an electric heated blast drying oven. After keeping it at 80 degrees Celsius for 1 day, it is naturally cooled to room temperature, and a large number of orange-yellow block crystals appear. After washing the obtained crystals with acetonitrile and drying at room temperature, the copper-silver nanocluster material is obtained, which belongs to the tetragonal system and has a yield of 82% based on acetylene silver.

[0028] The present invention is simple to operate and can prepare thiacalix[4]arene-protected copper-silver nanocluster catalyst materials by a one-pot solvothermal method. Figure 1 and Figure 2 As shown, the molecular structure of the copper-silver nanocluster material consists of a truncated cubic inorganic silver core and peripheral ligands. The large ligands cover the larger

[100] face of the cube in the core, and the small-sized ligands cover the smaller

[110] face of the cube, forming a double hydrophobic protective shell. The silver atoms on the truncated

[111] face are exposed, realizing the synthesis of silver nanocluster materials that take into account both stability and activity. The crystal system of crystal crystallization is closely related to the reaction temperature, wherein the higher the temperature, the higher the symmetry of the crystal system, i.e., 80 degrees is a tetragonal phase, 90 degrees is a trigonal phase, and 100 degrees is a cubic phase.

[0029] The CO2RR activity of the copper-silver nanocluster catalyst material of the present invention was evaluated in a CO2-saturated 1 M KCl (pH = 4.2) solution. Figure 3 As shown, the current density in a carbon dioxide atmosphere is twice that in an Ar atmosphere, indicating that the copper-silver nanocluster catalyst has catalytic activity for CO2 reduction.

[0030] The copper-silver nanocluster catalyst material of the present invention, under the condition of potassium chloride as electrolyte, at a potential of -0.95 to -1.25 V vs RHE, the reduction product CO is distributed in a volcano-like manner, and can maintain a CO Faraday efficiency of more than 80%, especially at a voltage of -1.15 V vs RHE, it can reach a CO Faraday efficiency of 97.76%. Figure 4 shown.

[0031] The copper-silver nanocluster catalyst material of the present invention can achieve 100 mA cm in a flow cell. -2 ~300 mAcm -2 Even at high current density, the CO Faradaic efficiency can reach over 70%. Figure 5 As shown, Figure 5 The middle bar graph is the CO Faraday efficiency, and the dotted line graph is the CO partial current density.

[0032] The copper-silver nanocluster catalyst material of the present invention can remain stable after catalysis, as shown by X-ray powder diffraction patterns and Fourier transform infrared spectra, which prove that it has good stability. Figure 6 and Figure 7 shown. Figure 6 In the figure, a is the PXRD curve loaded on carbon paper after reaction, b is the PXRD curve before reaction, and c is the simulated PXRD curve; Figure 7 In the figure, d is the infrared spectrum before the reaction, and e is the infrared spectrum after the reaction.

Claims

1. A thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2, characterized by: The single molecule chemical formula of the copper-silver nanocluster material is: 312 H 372 Ag 54 Cu 24 O 153 S 56 ; The single molecule structure formula of copper-silver nanocluster material is: Cu 24 Ag 54 (TC4A)6(SO4) 32 ( t BuC≡C) 12 , where TC4A represents thiacalix[4]arene, t BuC≡C is tert-butylacetylene; The copper-silver nanocluster material crystallizes to produce the following three space groups: The first is a cubic crystal system with a space group of Pn-3 and a unit cell parameter of: a = 40.4478 , b = 40.4478 , c = 40.4478 , α = 90°, β = 90°, γ = 90°, V = 66173.6 ; The second is a trigonal system, space group R-3, unit cell parameter a = 28.878 , b = 28.878 , c = 66.254 , α = 90°, β = 90°, γ = 120°, V = 47849 ; The third is tetragonal system, space group P4 / mnc, unit cell parameter: a = 27.5065 , b = 27.5065 , c =46.6184 , α = 90°, β = 90°, γ = 90°, V = 35271.8 ; Among them, a, b, c represent the axial lengths of the three groups of unit cells, α, β, γ represent the axial angles of the crystal, and V represents the volume of each unit cell.

2. A method for preparing a thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2, which is used to prepare the thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2 as claimed in claim 1, characterized in that: Includes the following step, And the following steps are performed in sequence: Step 1, dissolving organic silver acetylene, copper sulfate pentahydrate and thiacalix[4]arene in a mixed solvent, and stirring to obtain a mixture; Step 2: Transfer the mixture in step 1 to the polytetrafluoroethylene liner of a stainless steel autoclave and cover it; Step 3: After tightening the stainless steel autoclave in step 2, transfer it to an electric hot air drying oven and keep it at 80 to 100 degrees Celsius for 1 to 3 days, then cool it naturally to room temperature, and take out the orange-yellow block crystals appearing in the polytetrafluoroethylene lining; Step 4: Wash the block crystals obtained in step 3 with acetonitrile and dry them at room temperature to obtain the copper-silver nanocluster material.

3. The method for preparing a thiacalix[4]arene-protected copper-silver nanocluster material for electroreduction of CO2 according to claim 2, characterized in that: The organic silver acetylide in step 1 is at least one of alkyl silver acetylide or phenyl silver acetylide.

4. The method for preparing a thiacalix[4]arene-protected copper-silver nanocluster material for electroreduction of CO2 according to claim 2, characterized in that: The thiacalix[4]arene in step 1 is at least one of 4-tert-butyl-thiacalix[4]arene, 4-phenyl-thiacalix[4]arene or thiacalix[4]arene.

5. The method for preparing a thiacalix[4]arene-protected copper-silver nanocluster material for electroreduction of CO2 according to claim 2, characterized in that: The mass ratio of copper sulfate pentahydrate, organic silver acetylene and thiacalixarene in the step 1 is 3:2:2 to 3:1:

1.

6. The method for preparing a thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2 according to claim 2, characterized in that: The mixed solvent in step 1 is a nitrogen-containing solvent, an alcohol and a third solvent, and the mass ratio of the three is 1:1:2 to 1:4:

4.

7. The method for preparing a thiacalix[4]arene-protected copper-silver nanocluster material for electroreduction of CO2 according to claim 6, characterized in that: The nitrogen-containing solvent is N,N-dimethylformamide or N,N-diethylformamide or N,N-dimethylacetamide; the alcohol is methanol or ethanol or n-butanol or isopropanol or n-propanol; the third solvent is acetonitrile or tetrahydrofuran or 1,4-dioxane.

8. A method for preparing a thiacalix[4]arene protected copper-silver nanocluster material for electroreduction of CO2 according to any one of claims 2, 5 or 6, characterized in that: The total mass of the copper sulfate pentahydrate, the organic silver acetylene and the thiacalix[4]arene is 50 mg to 100 mg, and the total volume of the mixed solvent used is 2 ml to 6 ml.

Citation Information

Patent Citations

  • Thiacalix[4]arene protected alkyne silver cluster material as well as preparation method and application thereof

    CN113718338A

  • Silver nano-cluster containing 50 cores and preparation method of silver nano-cluster

    CN115070030A

  • Silver nanocluster protected by metal ligand and preparation and remote laser ignition application thereof

    CN116396310A

  • Alloy metal nanocluster and preparation method and application thereof

    CN118165042A